2017
DOI: 10.1021/acscatal.6b03190
|View full text |Cite
|
Sign up to set email alerts
|

Tandem Site- and Size-Controlled Pd Nanoparticles for the Directed Hydrogenation of Furfural

Abstract: The conversion of biomass to useful chemical products requires precise catalytic properties to achieve the required activity, selectivity, and durability. Here we show, through optimized colloidal synthesis, the tandem control of Pd size and site availability for the directed hydrogenation of the bioderived intermediate furfural. Adjusting the temperature of colloidal reduction dictates the size of Pd nanoparticles; in some instances ultrasmall clusters of <20 atoms are achieved. However, changing the solvent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
92
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 118 publications
(105 citation statements)
references
References 50 publications
(80 reference statements)
9
92
0
Order By: Relevance
“…Pd‐based catalysts have also shown higher efficacy towards different hydrogenating reactions including hydrogenolysis of furfural and HMF . In heterogeneous catalysis, reactions occur on the surface of nanoparticles, therefore, the catalytic activity and selectivity of nanoparticles highly depend on the shape, size and availability of the active site on the nanoparticles.…”
Section: Catalytic Hydrogenation And/or Hydrogenolysis Of Biomass‐dermentioning
confidence: 99%
See 1 more Smart Citation
“…Pd‐based catalysts have also shown higher efficacy towards different hydrogenating reactions including hydrogenolysis of furfural and HMF . In heterogeneous catalysis, reactions occur on the surface of nanoparticles, therefore, the catalytic activity and selectivity of nanoparticles highly depend on the shape, size and availability of the active site on the nanoparticles.…”
Section: Catalytic Hydrogenation And/or Hydrogenolysis Of Biomass‐dermentioning
confidence: 99%
“…In this direction, Rogers et al. synthesised Pd nanoparticles with tuned size and active reaction sites using a combination of solvent and reduction temperature . Results revealed that at very low temperature (1 °C) in water, ultrasmall cluster of <20 Pd atoms with a size of 2.5 nm was formed, with further decrease in the temperature to −30 °C resulted in the formation of 1.4 nm particles .…”
Section: Catalytic Hydrogenation And/or Hydrogenolysis Of Biomass‐dermentioning
confidence: 99%
“…Conversely, the available sites that correspond to the bridge‐bonded and 3‐fold CO absorption are able to bind the HMF through both furan ring and the η 1 (C) mode of aldehyde group. This flat adsorption of HMF is beneficial to decarbonylation of aldehyde group ,,. Therefore, the superior activity of Pd/Al 2 O 3 catalyst for production of FOL is inferred to the decarbonylation of aldehyde group on the accessible facets sites of Pd NPs.…”
Section: Resultsmentioning
confidence: 99%
“…The different binding models of HMF have been shown in Figure , as previous studies proposed that the corner sites of Pd NPs tend to bind furan ring in a perpendicular orientation, rather than the flat across the surface. In this stance, the aldehyde group adsorbs on the surface of Pd by the η 2 (C, O) configuration, which is unfavorable for decarbonylation ,…”
Section: Resultsmentioning
confidence: 99%
“…[23] In general, the formation of well-defined Pd nanocrystals can be divided into three major steps in one-pot syntheses: i) nucleation from metal ions; ii) evolution into seeds with well-defined internal structures; and iii) growth into nanocrystals with distinctive shapes. [23] In general, the formation of well-defined Pd nanocrystals can be divided into three major steps in one-pot syntheses: i) nucleation from metal ions; ii) evolution into seeds with well-defined internal structures; and iii) growth into nanocrystals with distinctive shapes.…”
Section: Introductionmentioning
confidence: 99%